Achieving High Thermoelectric Performance by Introducing 3D Atomically Thin Conductive Framework in Porous Bi2Te2.7Se0.3‐Carbon Nanotube Hybrids. (14th July 2020) - Li, Shuankui; Wang, Rui; Zhu, Weiming; Chu, Mihai; Huang, Zhongyuan; Zhang, Yanjun; Zhao, Wenguang; Liu, Fusheng; Luo, Jun; Xiao, Yinguo; Pan, Feng
Abstract: Fabricating thermoelectric (TE) materials with porous structure is an effective approach to reduce lattice thermal conductivity; however, the electrical conductivity is usually severely sacrificed. In this work, a high performance porous Bi2 Te2.7 Se0.3 ‐carbon nanotube (BTS‐CNTs) thermoelectric hybrid is prepared by introducing atomically thin BTS conductive networks on the BTS‐CNT interface, which simultaneously possess ultralow lattice thermal conductivity and high electrical conductivity. The 3D conductive framework built by atomically thin BTS layers on CNTs enables the creation of an intimate contact with bulk BTS and serves as a fast pathway of the electric conductivity, resulting in high electrical conductivity. Meanwhile, the phonon scattering around nanopore wall is greatly enhanced, and the lattice thermal conductivity is found to be as low as 0.19 W m −1 K −1, which is close to the minimal lattice thermal conductivity according to Debye–Cahill model. Consequently, the porous BTS/CNTs hybrid displays a high ZT value of about 1.2, which is 65% higher than that of fully dense pristine BTS. The present work demonstrates a novel and practical approach to design and fabricate high performance porous TE materials through an unconventional sacrificial template method. Abstract : A high‐performance porous Bi2 Te2.7 Se0.3 ‐carbon nanotube (BTS‐CNT) thermoelectric hybrid is prepared by introducing atomically thin BTS conductive networks on the BTS‐CNT interface, which simultaneously possess ultralow lattice thermal conductivity and high electrical conductivity. The porous BTS/CNTs hybrids display a high ZT value of ≈1.2, which is 65% higher than that of fully dense pristine BTS.